2022
DOI: 10.1007/s10238-022-00936-8
|View full text |Cite
|
Sign up to set email alerts
|

Presepsin levels and COVID-19 severity: a systematic review and meta-analysis

Abstract: Plasmatic presepsin (PSP) is a novel biomarker reported to be useful for sepsis diagnosis and prognosis. During the pandemic, only few studies highlighted a possible correlation between PSP and COVID-19 severity, but results remain inconsistent. The present study aims to establish the correlation between PSP and COVID-19 severity. English-language papers assessing a correlation between COVID-19 and PSP from MEDLINE, PubMed, Google Scholar, Cochrane Library, MeSH, LitCovid NLM, EMBASE, CINAHL Plus and the World… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
2
11
1
Order By: Relevance
“…In some studies, the absence of a significant difference in those with positive cultures, may have been due to reasons such as the amount and quality of the sample, the severity of the infection, and the inadequacy of the laboratory. 6 According to the results of the systematic meta-analysis conducted by Guarino et al 19 a significant correlation was found between the severity of COVID-19 and presepsin level. Similarly, Kim et al 20 found a significant correlation between the severity of COVID-19 and presepsin level.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, the absence of a significant difference in those with positive cultures, may have been due to reasons such as the amount and quality of the sample, the severity of the infection, and the inadequacy of the laboratory. 6 According to the results of the systematic meta-analysis conducted by Guarino et al 19 a significant correlation was found between the severity of COVID-19 and presepsin level. Similarly, Kim et al 20 found a significant correlation between the severity of COVID-19 and presepsin level.…”
Section: Discussionmentioning
confidence: 99%
“…Presepsin is a biomarker that has been studied in relation to sepsis, a potentially life-threatening condition that occurs when the body’s response to infection causes damage to its own tissues and organs. There is research evidence that suggests that presepsin levels may be elevated in individuals with severe COVID-19, particularly those who develop sepsis as a complication of the disease [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that PSP levels were increased by 2.74-fold in COVID-19 patients with severe illness compared to those without. Guarino et al [62] published a meta-analysis of data from 707 patients from 15 studies, and they found that the pooled mean difference of PSP levels between high-and low-severity COVID-19 patients was 441.70 pg/ml (95%CI: 150.40-732.99 pg/ml). In another interesting study published by Dell'Aquila and colleagues [63], in a population of COVID-19 patients with acute respiratory failure in an emergency department, PSP was accurate predictor of 30-day mortality.…”
Section: Presepsin and Covid-19mentioning
confidence: 99%